2007 10th International Conference on Computer and Information Technology 2007
DOI: 10.1109/iccitechn.2007.4579377
|View full text |Cite
|
Sign up to set email alerts
|

5D virtual constructions: Designer/constructor’s perspective

Abstract: The construction activity level intricacy makes the whole construction process quite complicated and difficult for planners and builders. 4D (3D+Time) construction planning is a promising area, and it presents the ability to represent the construction process with the additional sequential dimension. It makes the virtual models easy to analyze and plan for the sequence of activities.Traditionally, architectural/construction engineering and technology education, especially construction scheduling has been depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…In BIM, integrating the cost element is represented by the fifth dimension (5D), which for many firms, can be recognised as a competitive approach towards cost management (Smith, 2014). BIM offers the ability for QSs to take-off, count and measure directly from a regularly updated model through 5D BIM applications by linking the model to estimating software (Haque and Mishra, 2007). With the tedious task of quantification in some sense being automated and effortless, it allows QS to pay attention to and provide expertise on other project-specific factors, e.g.…”
Section: Bim For Qss: 5d Bim Application Outputsmentioning
confidence: 99%
“…In BIM, integrating the cost element is represented by the fifth dimension (5D), which for many firms, can be recognised as a competitive approach towards cost management (Smith, 2014). BIM offers the ability for QSs to take-off, count and measure directly from a regularly updated model through 5D BIM applications by linking the model to estimating software (Haque and Mishra, 2007). With the tedious task of quantification in some sense being automated and effortless, it allows QS to pay attention to and provide expertise on other project-specific factors, e.g.…”
Section: Bim For Qss: 5d Bim Application Outputsmentioning
confidence: 99%
“…Within the BIM model, the integration of the cost aspect is provided by the 5D dimension, which by several consulting organisations, can be seen as an advantage towards cost management [31]. The model gives the project manager the capabilities to measure, take-offs and count straight from a regular updated BIM model through 5D BIM application by connecting the estimating software and the model [14]. According to [4], with the dragging process of qualification in some instances being effortless and automated, this provides more time to the project manager to give for more focus and give the knowledge on other project specification e.g.…”
Section: Bim For the Qs: 5d Bim Applicationmentioning
confidence: 99%
“…BIM automatically presents data both visually and analytically, information is clearer and easier to understand, and 4D models serve as platform for detection of potential conflicts and risk analysis [10] Having observed that an intrinsic limit of 4D visualization in BIM models is the lack of economic features, we propose system to integrate BIM technology and EVM, following Haque [10] and Jrade and Lessard's intuition [11]. The basis of the study comes from the idea of Construction Site Information Model (Co.S.I.M.)…”
Section: Literary Reviewmentioning
confidence: 99%